2001
DOI: 10.1073/pnas.98.3.1277
|View full text |Cite
|
Sign up to set email alerts
|

Brain serotonin dysfunction accounts for aggression in male mice lacking neuronal nitric oxide synthase

Abstract: Genetically engineered mice with targeted disruption of the neuronal nitric oxide synthase (nNOS) gene established the inhibitory role of nitric oxide (NO) in male impulsive aggressive behavior. This was later confirmed by using selective nNOS inhibitors in male wild-type mice. The molecular mechanisms accounting for the aggressive behavior caused by the lack of neuronally derived NO is not known. Recent studies suggest that central serotonergic neuronal circuits and particularly 5-HT1A and 5-HT1B receptors pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(43 citation statements)
references
References 28 publications
1
41
0
1
Order By: Relevance
“…64 Recent evidence implicates selective decreases in serotonic (5-HT) turnover and deficient 5-HT 1a and 5-HT 1b receptor function in these mice. [65][66][67] Of great interest for the current work, this aggressive behavior required testosterone, but serum testosterone levels did not vary between the (ϩ/ϩ) and (Ϫ/Ϫ) mice. It is appreciated that although testosterone is required for normal erectile function, it is permission and does not play a direct role.…”
Section: Discussionmentioning
confidence: 99%
“…64 Recent evidence implicates selective decreases in serotonic (5-HT) turnover and deficient 5-HT 1a and 5-HT 1b receptor function in these mice. [65][66][67] Of great interest for the current work, this aggressive behavior required testosterone, but serum testosterone levels did not vary between the (ϩ/ϩ) and (Ϫ/Ϫ) mice. It is appreciated that although testosterone is required for normal erectile function, it is permission and does not play a direct role.…”
Section: Discussionmentioning
confidence: 99%
“…This notion is further supported by the finding that NOS-I knockout mice feature marked changes in serotonergic function: 5HT turnover is impaired, 5HT receptors are desensitized, and 5HTT expression in the brain stem neurons is decreased. 73 Regarding dopaminergic signaling, it has been shown that NO regulates striatal output by modulating the firing pattern of striatal neurons. 74 Taken together, NO appears to be a link between glutamatergic transmission on the one hand and monoaminergic system on the other, thus being centered in key pathways previously shown to be involved in the pathophysiology of SCZ.…”
Section: -43mentioning
confidence: 99%
“…Most research on the role of NO in social behaviours has focused on aggression [5,13,29,31,41]. Male mice lacking the gene that encodes nNOS (nNOS-/-) are highly aggressive and do not relent in response to submissive postures of wildtype (WT) males [29].…”
Section: Introductionmentioning
confidence: 99%